Recent progress of Bioinspired Hydrogel-based delivery system for endometrial repair - Dong, Rong; Ma, Saihua; Zhao, Xiaoli; Wang, Baojuan; Roy, Mridul; Yao, Lu; Xia, Tian; Liu, Yanting (Frontiers in Bioengineering and Biotechnology, 2022)
Endometrial injury is the main fact leading to infertility. Current treatments of endometrial injury present many problems, such as unable to achieve desired effects due to low retention and the inherent potential risk of injury. Hydrogel is a kind of bioinspired superhydrophilic materials with unique characteristics, such as excellent biocompatibility, biodegradability, porosity, swelling, and cross-linkage. These unique physiochemical properties of bioinspired hydrogels enable their promising application as novel delivery platform and alternative therapies for endometrial injury. In this mini review, we summarize the recent advances in bioinispred hydrogel-based delivery system for endometrial repair, including as a post-operative physical barrier and therapeutic delivery system. In addition, present status, limitations, and future perspectives are also discussed.